A Companion to modern art - 4 0 16; Meecham, Pam; 5 (Hoboken, NJ : John Wiley & Sons, 2018)
Featuring contributions from a diverse range of established and emerging international scholars. art historians, curators, artists, and cultural critics, A Companion to Modern Art critically examines the complicated and often contentious legacies of Modern Art and modernism within a still globalizing present. This collection of original essays explores topics including Modern Art's interdisciplinarity, the historic and contemporary understanding of avant-garde works and exhibitions, Modern Art and colonialism, constructions of the artist, and Modern Art education, Looking again at modernism's central tropes this volume also offers re-evaluations of modernism and classicism, primitivism, the role of the archaic in the modern, and reflections on Nietzschean aesthetics and the modern imagination. Readers can expect to gain further understanding of Modern Art's foundational philosophic ideas and practices, new assessments of key artists such as Cezanne and Picasso, as well as debates around less familiar artists.;Pis Professor of Museum Studies at the UCL Institute of Education, where she conducts research into institutional histories and the display of modernism. --Book Jacket.
Ancient & Modern -- Displaying the Modern -- Re-assessments : Modernism and Globalization -- Locating Modernism : Multiple Modernisms and National Identities -- The Modern Artist, the Modern Child and a Modern Art Education.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on January 09, 2018).
Keywords: 2 -- 0; 6; History;General. -- Art, Modern.;ART; 20; Electronic books. -- 2